2015
DOI: 10.4049/jimmunol.1402562
|View full text |Cite
|
Sign up to set email alerts
|

An Epistatic Interaction between Themis1 and Vav1 Modulates Regulatory T Cell Function and Inflammatory Bowel Disease Development

Abstract: The development of inflammatory diseases depends on complex interactions between several genes and various environmental factors. Discovering new genetic risk factors and understanding the mechanisms whereby they influence disease development is of paramount importance. We previously reported that deficiency in Themis1, a new actor of TCR signaling, impairs regulatory T cell (Treg) function and predisposes Brown–Norway (BN) rats to spontaneous inflammatory bowel disease (IBD). In this study, we reveal that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Among the differentially expressed genes were genes of the TGF-b signaling pathway (Tgfbi and Smad3), the IL-10 receptor a chain (Il10ra), several genes that had previously been linked to Treg cells found in visceral adipose tissue (Ccr1 and Cd36), and several genes known to be involved in Treg cell functionality and suppressive activity (Themis2 and Runx3; see Fig E6, E). [37][38][39] We conclude from these data that epigenetic marks leading to stable expression of Foxp3 and the definitive lineage commitment of Treg cells, along with differential gene expression caused by extract exposure, reflect and likely mediate the suppressive effects of H pylori-specific perinatal interventions on allergic airway inflammation.…”
Section: Systemic Depletion Of Treg Cells Reduces the Protective Effementioning
confidence: 80%
“…Among the differentially expressed genes were genes of the TGF-b signaling pathway (Tgfbi and Smad3), the IL-10 receptor a chain (Il10ra), several genes that had previously been linked to Treg cells found in visceral adipose tissue (Ccr1 and Cd36), and several genes known to be involved in Treg cell functionality and suppressive activity (Themis2 and Runx3; see Fig E6, E). [37][38][39] We conclude from these data that epigenetic marks leading to stable expression of Foxp3 and the definitive lineage commitment of Treg cells, along with differential gene expression caused by extract exposure, reflect and likely mediate the suppressive effects of H pylori-specific perinatal interventions on allergic airway inflammation.…”
Section: Systemic Depletion Of Treg Cells Reduces the Protective Effementioning
confidence: 80%
“…Alternatively, it could be hypothesized that the positive effect of Themis1 on Vav1 may be preponderant in these cells, and may counterbalance potential inhibitory function of Themis1 through SHP-1. Supporting this interpretation, we previously showed that the combined deficiency of Themis1 and Vav1 in Brown-Norway rats impairs the suppressive function of Treg, despite normal levels of Foxp3 expression, and leads to the spontaneous development of IBD (54,55). This highlights that the cooperation between Themis1 and Vav1 is required for proper Treg function.…”
Section: Discussionmentioning
confidence: 69%
“…In the past, several genetic studies have investigated epistasis on IBD [ 6 , 7 , 9–11 , 25 ]. We compared them to our results at the gene level, the minimal functional unit at which we expect genetic studies to converge.…”
Section: Discussionmentioning
confidence: 99%